Iodine-129 and Iodine-127 as an environmental tracer for salinity origin in groundwater - Tan, Sunshine Petal V.
Monitoring groundwater vulnerability from salinity contamination is important in order to manage the sustainability of supplying clean water to the ever-increasing demand of the population. The aim of this study is to investigate origin of anomalously high salinities locally found in Pampanga by using Iodine-129 and Iodine-127 to compliment and add information from the traditional use of hydrogeochemical and stable water isotopes parameters. Iodine-129 (129I, half-life: 15.7 million years), a radioisotope of iodine, and stable isotope Iodine-127 (127I), with the integration of hydrogeochemical properties and stable water isotopes (d2H and d18O), were used to identify possible sources of salinity in groundwater. During the wet season in July 2017, one hundred four (104) water samples were taken from production wells (6 to 300) meters below ground level), rivers and precipitation in Pampanga, one of the regions in the Philippines that heavily rely on groundwater for freshwater source. Hydrogeochemical and stable water isotope (d2H and d18O) properties were measured in Mines and Geosciences Bureau (MGB) and Philippine Nuclear Research Institute (PNRI) respectively. The water samples for Iodine-129 and Iodine-127 were prepared in PNRI and were measured in MALT, University of Tokyo using accelerator mass spectrometry (AMS) and inductively coupled plasma mass spectrometry (ICP-MS). Hydrogeochemical results showed Na-HCO3 as dominant water type. Further analysis traced groundwater salinization from silicate weathering along with dissolution of rock forming materials. Stable water isotopes (SWI) suggest direct evaporation plays a significant role in elevating groundwater salinity in some regions in Pampanga. Hydrogeochemical and stable water isotopes seawater mixing indicators identified 7 groundwater samples with anomalous salinity. These samples were further investigated using Iodine-129 and Iodine-127 isotopes by generating the following three (3) graphs: Iodine-129 vs. Iodine-127 vs. Chloride and ¹²?I/¹²7I ratio vs. 1/¹²7. The results from the graphs were able to confirm and classify salinization origin whether from seawater intrusion, connate water, evaporative origin (ie. river, fishpond) and even contamination (ie. wastewater). Out of the 7 groundwater samples, one (1) sample, LOB01 (Candaba), was identified to be from connate water, 2 samples, LOB11 (Magalang) and MBP27 (San Simon), are from contamination source and the last 4 samples, LOB06 (Candaba), JGG06 (Macabebe), MBP16 (Apalit) and MBP18 (Apalit) are from river origin. Based on the three graphs, there are no groundwater samples sampled in Pampanga for this study that implied seawater mixing due to excessive pumping exceeding recharge or due to tidal excursion/tidal influx. The results showed the applicability of Iodine-129 and Iodine-127 to trace the origin of salinity in groundwater. Iodine-129 and Iodine-127 provides parameters in groundwater that cannot be easily characterized by major ions or stable water isotopes. In addition, both iodine isotopes demonstrated its utility for groundwater age. Groundwater in Pampanga was estimated to be between 21-162 years as of 2019, with a mean age of 69 years. Additionally, using mass balance equation based on SWI, the three rivers sampled, Pampanga River, Pasig-Potrero River, and Matalaba River, accounted for 40-45% and precipitation accounted for 55-60% of the groundwater recharge in its respective sampled location in Pampanga. The information produced in this research will be useful in groundwater management by commercial and government agen